Physicochemical properties of polysaccharides from Dendrobium officinale by fractional precipitation and their preliminary antioxidant and anti-HepG2 cells activities in vitro - Xing, Shangping (Chem Cent J, 2018)
BACKGROUND: Dendrobium officinale as a precious traditional Chinese herb is widely used in medicines and health supplements. Thus the extraction, purification and biological activities of polysaccharides from the stem of Dendrobium officinale have significant meaning on theory and application value. METHODS: The crude Dendrobium officinale polysaccharide (DOP) was obtained by hot water extraction- ethanol precipitation method, and four new polysaccharide fractions (DOP-40, DOP-50, DOP-60, and DOP-70) were further obtained from the crude DOP by fractional precipitation with ethanol method, then four fractions were further purified by Toyopearl-H65F gel resin. The molecular weight and monosaccharide composition of four purified fractions were determined by high performance anion exchange chromatography and high performance liquid chromatography. The antioxidant activities of them were evaluated by the reducing power assay, and the superoxide anion, 2,2-diphenyl-1-picrylhydrazyl (DPPH), and hydroxyl free radicals scavenging assays, respectively. Finally, the anticancer activities of them were investigated via the MTT assay and the western blot analysis using HepG2 cells. RESULTS: Among these four purified fractions were mainly composed of d-mannose and d-glucose with different molar ratios, and their average molecular weights were 999, 657, 243 and 50.3 kDa, respectively. What’s more, DOP-70 always exhibited the strongest antioxidant and anticancer activities, while DOP-40 and DOP-60 showed very close antioxidant and anticancer activities which were better than that of DOP-50. The western blotting analysis also showed that DOP-40, DOP-60, and DOP-70 induced apoptosis in HepG2 human liver cancer cells through the Bcl-2 and Bax-dependent pathway. CONCLUSIONS: Fractional precipitation with ethanol could successfully apply to extract four new polysaccharide fractions from Dendrobium officinale stems, and the polysaccharide fractions possessed efficient antioxidant and anticancer activities, especially DOP-70.